Analisis Pemahaman Masyarakat Desa Lam Ara Tunong terhadap Kesadaran akan Kepedulian Lingkungan - Phonna, Nie Zahara; Afinni, Ummi Nur; Mardiah, Ros; Az-zahra, Nabila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Lam Ara Tunong Village is located in a rural area that has distinctive social and cultural characteristics. In this analysis, the understanding of the Lam Ara Tunong village community regarding their awareness and concern for the environment will be examined. This analysis aims to investigate the understanding and concern of the Lam Ara Tunong village community for the environment. Awareness and concern for the environment are key factors in maintaining ecosystem sustainability and natural balance. This study used a survey method, the survey was conducted by distributing questionnaires in the form of a Google form to be filled out by respondents. This research hopes to provide insight and open the horizons of thinking of the people of Lam Ara Tunong village. The population taken is from the village of Lam Ara Tunong. The sample used in this study was 60 people who were local people. Data collection techniques in this study used the Guttman scale. The instrument used was a random sampling technique. Furthermore, the results of this questionnaire data were analyzed by looking at the score of the choices. Keywords: Analysis of understanding, awareness, community concern